Extraintestinal manifestations in inflammatory bowel disease - Danese, Silvio (World J Gastroenterol, 2005)
Inflammatory bowel diseases (IBD) can be really considered to be systemic diseases since they are often associated with extraintestinal manifestations, complications, and other autoimmune disorders. Indeed, physicians who care for patients with ulcerative colitis and Crohn’s disease, the two major forms of IBD, face a new clinical challenge every day, worsened by the very frequent rate of extraintestinal complications. The goal of this review is to provide an overview and an update on the extraintestinal complications occurring in IBD. Indeed, this paper highlights how virtually almost every organ system can be involved, principally eyes, skin, joints, kidneys, liver and biliary tracts, and vasculature (or vascular system) are the most common sites of systemic IBD and their involvement is dependent on different mechanisms.